The Effects of Backward Adjustable Thoracic Support in Wheelchair on Spinal Curvature and Back Muscle Activation for Elderly People - Li, Chun-Ting (PLoS One, 2014)
OBJECTIVES: To investigate the effects of backward adjustable thoracic support on spinal curvature and back muscle activation during wheelchair sitting. METHODS: Twenty elderly people were recruited for this study. The backward adjustable thoracic support sitting posture was compared with the slumped, normal, and lumbar support sitting postures. Spinal curvatures (pelvic, lumbar, and thoracic angles) and muscle activations of 4 back muscles on both sides (maximal voluntary isometric contraction of the lumbar multifidus, lumbar erector spinae, iliocostalis lumborum pars thoracis, and thoracic erector spinae at T9) were measured and compared between the different sitting postures using one-way analysis of variance with repeated measures. RESULTS: The backward adjustable thoracic support sitting posture showed a relatively neutral pelvic tilt (−0.32±4.80°) when compared with the slumped (22.84±5.27°) and lumbar support (−8.97±3.31°) sitting postures (P<0.001), and showed relatively higher lumbar lordosis (−23.38±6.50°) when compared with the slumped (14.77±7.83°), normal (0.44±7.47°), and lumbar support (−16.76±4.77°) sitting postures (P<0.05). It also showed relatively lower back muscle activity when compared with the normal and lumbar support sitting postures (P<0.05). CONCLUSIONS: The backward adjustable thoracic support sitting concept was suggested because it maintains a more neutral pelvic tilt, higher lumbar lordosis, and lower back muscle activation, which may help maintain a better sitting posture and reduce the risk of back pain.